Measures of Success: Evaluating University of British Columbia's Master of Archival Studies Program - Peters, Evelyn (Archivaria, 1998)
This article presents the findings of a survey of the attitudes of persons who have attended the Master of Archival Studies Program at the University of British Columbia towards the program's effectiveness in preparing them to enter the workforce as archivists or records managers. The findings suggest that, on the whole, graduates are satisfied with the preparation that the program provided, but that they view certain aspects of the program as less effective than others. The article argues that, in general, the success of any professional educational program in preparing its graduates to join the workforce is both a measure of that program's efficacy and the given profession's level of development. It also proposes that it is important to carefully examine the archival education currently offered in order to continue developing curricula appropriate to those entering the archives profession. RÉSUMÉ Cet article présente les résultats d'une enquête portant sur l'opinion des personnes qui ont été inscrites au programme de maîtrise en archivistique de l'Université de la Colombie-Britannique relativement à sa capacité à les préparer au marché du travail comme archivistes ou gestionnaires des documents. Les résultats indiquent que, dans l'ensemble, les finissants sont satisfaits de la préparation offerte par le programme bien qu'ils en considèrent certains éléments comme moins efficients que d'autres. L'article suggère que le succès de tout programme de formation professionnelle à préparer ses finissants à rallier le marché du travail est, règle générale, un indicateur à la fois de l'efficience du programme et du niveau de développement atteint au sein d'une profession. On suggère de plus qu'il est important de bien examiner la formation présentement offerte en archivistique pour continuer à développer des programmes adaptés à ceux qui embrassent la profession.